Modification of g‐C3N4 Photocatalyst with Flower‐like ReS2 for Highly Efficient Photocatalytic Hydrogen Evolution. Issue 24 (28th October 2020) - Xing, Chuanwang; Zhao, Haitao; Yu, Guiyang; Guo, Luyan; Hu, Yujia; Chen, Ting; Jiang, Lilin; Li, Xiyou
Abstract: Heterojunction strategy has proven to be an effective approach for overcoming the quick photoexcited charge carrier recombination of graphitic carbon nitride (g‐C3 N4 ) and facilitating its photocatalytic performances. Bearing the merits of transition metal dichalcogenides (TMDs) in mind, in this work, a novel flower‐like ReS2 coupled with layered g‐C3 N4 was constructed via a facile hydrothermal route. The hybrid ReS2 /g‐C3 N4 catalysts create excellent photocatalytic hydrogen evolution without any additional co‐catalyst. Under visible‐light irradiation, the optimized 3 wt % ReS2 /g‐C3 N4 heterojunction exhibited a hydrogen evolution rate 8 times that of pristine g‐C3 N4, maintaining a stable heterojunction after multiple photocatalytic cycles. ReS2 /g‐C3 N4 integrates the merits of both the configuration of a heterojunction and the formation of spatially conductive network, which effectively accelerate the transfer of photoinduced carrier. This work not only presents a marked ReS2 /g‐C3 N4 heterojunction photocatalyst, but provides more possibility for expanding applications in electrocatalysis, photothermal catalysis and energy storage. Abstract : Photocatalysis : A novel three‐dimensional flower‐like ReS2 coupled with layered g‐C3 N4 exhibits obviously improved photocatalytic hydrogen evolution activity under visible light irradiation. Without any additional co‐catalyst, the optimized 3 wt % ReS2 /g‐C3 N4 heterojunction exhibited 8 times higher hydrogen evolution rate than that of pristine g‐C3 N4 and maintained favourable stability during multiple photocatalytic cycles. This work enriches the heterojunction strategy of TMDs‐modified semiconductor, which may open a door for versatile applications in the fields of thermocatalysis, photoelectrocatalysis, optoelectronic devices and supercapacitor.